Geoquímica, geocronologia e contexto geotectônico do magmatismo máfico associado ao Feixe de Fraturas Colatina, Estado Espirito Santo - Juliane Belem Figueiredo Fleck (2014)
The Colatina fracture zone is a protracted, 250 km-long, 30 km-wide, medium- to high-angle dip, NNW-trending structure, clearly shown by remote sensing images on the on shore basement region of the hydrocarbon-rich, Mesozoic-Cenozoic Espírito Santo basin, southeastern Brazil. This basement, located in the back-arc region of the Araçuaí orogen, includes Ediacaran paragneisses (Nova Venécia complex) and related granites (G2 and G3 supersuites), cut by a myriad of Cambrian (525490 Ma) post-collisional plutons (G5 supersuite), which form the host rocks of a mafic dyke swarm (Fundão suite) emplaced along the Colatina fracture system. Field evidence suggest two tectonic events related to the Fundão suite: i) dikes emplacement took place during a tractive phase, which form plumose joints; ii) low rake strike lineation imprinted on fracture coats composed of carbonate, chlorite, quartz, mica and/or sulfide, and along sheared dike contacts indicate the second tectonic event. We present new litochemical and isotopic (Ar-Ar, Sm-Nd, Sr, and U-Pb) datasets from the mafic dikes, as well as from their host rocks, compared with a thorough data compilation from the literature. The mafic lithotypes are generally olivine-bearing and comprise fine-grained gabbro, porphyritic to equigranular dolerite, porphyritic and aphanitic to vitreous basalt varieties. Geochemical attributes suggest a within-plate, crustal-contaminated, tholleiitic series, which parental magma evolved from the lithospheric mantle. U-Pb (SHRIMP and LA-MC-ICP-MS) ages from zircon and titanite neoformed crystals, and recrystallized grain domains suggest magmatic crystallization from ca. 520 Ma to ca. 490 Ma. Inherited zircon grains record the whole history of the basement. These data fit with the timing evolution of the G5 supersuite, which represents a post-collisional (late orogenic) magmatic event related to the gravitational collapse of the Araçuaí orogen. Accordingly, the Fundão suite is coeval with the G5 supersuite, representing intermediate to shallow crust emplacement of basaltic magma related to underplating of lithospheric mantle magma. This implies in fast exhumation rates, which have been quoted in the literature. Ar-Ar data from whole-rock and plagioclase samples suggest isotopic resetting probably related to the Atlantic opening.